Private libraries of famous persons in Siberia and the Far East (end XVIII – middle XX centuries) - E. B. Artemyeva (Библиосфера)
The article provides information on the private libraries of famous persons in Siberia and the Far East, who were not directly related to books by the nature of their activities.